Pemberian Pupuk Limbah Biogas Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Di Pre-Nursery - Khoirudin, Al Hikmatu; Sampoerno, Sampoerno; Venita, Yunel (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The oil palm (Elaeis guineensis Jacq.) is a plant that has a fairly high economic value because it produces the world's largest vegetable oils. In Indonesia oil palm has a significance for the national economy, in addition to being able to create jobs as well as a source of obtaining country (foreign country). This research aims to know the influence of biogas liquid waste against the growth of seedlings of Palm and get a dose of the best nursery Pre-Nursery. Research using randomized complete design (RAL) non factorial consists of 5 treatments and four replicates. As for the treatment of: P0: 0 ml liquid waste biogas/plant, P1: 20 ml liquid waste/biogas plants, P2: 40 ml liquid waste/biogas plants, P3: 60 ml liquid waste biogas/plant, P4: 80 ml liquid waste/biogas plants. Based on the results of the analysis of the variety that the average grant of liquid waste biogas influential real against the high seeds, number of seeds, leaves diameter of seedlings, seeds, and dry weight ratio of oil palm seedlings root header in Pre-Nursery age ≤ 3 months. The best doses against the growth of seedlings of Palm Pre Nursery-aged ≤ 3 months i.e. 80 ml/plant. Key words: oil palm, waste biogas